Analisis Kinerja Bank Pembiayaan Rakyat Syariah (Bprs) Di Provinsi Bengkulu Dengan Pendekatan Sharia Maqasid Index (SMI) - Afrianty, Nonie (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study aims to analyze the performance of the BPRS by looking at how much the level of achievement maslahah (welfare) in the sharia maqasid as well as comparing the performance among Islamic People’s Financing Banks (BPRS) in Bengkulu Province with the Sharia Maqasid Index (SMI) approach. This research is a quantitative research with a descriptive approach. The population of this study is BPRS in Bengkulu Province which was recorded during the period March 2016 to March 2017. The sampling technique in this study was conduced by purposive sampling. The results of this study is BRRS Safir har superior performance with a value of 16,35% while BPRS Muamalat Harkat with a value of 15,64%. This show that BPRS Safir is a sharia banking institution that is not only profir oriented but there us education, justice and community welfare values that reflect the size of the non-profit benefits in accordance with the objectives of Islamic banks.